2016
DOI: 10.1177/0032321716651653
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for Godot? Welfare Attitudes in Portugal before and after the Financial Crisis

Abstract: Do attitudes towards the welfare state change in response to economic crises? Addressing this question is sometimes difficult because of the lack of longitudinal data. This article deals with this empirical challenge using survey data from the 2008 European Social Survey and from our own follow-up survey of Spring 2013 to track welfare attitudes at the brink and at the peak of the socioeconomic crisis in one of the hardest hit countries: Portugal. The literature on social policy preferences predicts an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Regarding the political attitudes and political action, Magalhães (2005) found that citizens are increasingly dissatisfied with the democratic performance. This may be due to a negative perception of political responsiveness of representative institutions (Torcal, 2014) and the economic crisis in Portugal one decade ago that negatively influenced the political attitude (Brito Vieira et al, 2017) and the political trust (van der Meer and Hakhverdian, 2017). The e-participation tools oriented for decision making may open an interesting opportunity to allow the citizens themselves to propose and decide on local issues, which could help to recover the trust and satisfaction in representative institutions.…”
Section: Data Collectionmentioning
confidence: 99%
“…Regarding the political attitudes and political action, Magalhães (2005) found that citizens are increasingly dissatisfied with the democratic performance. This may be due to a negative perception of political responsiveness of representative institutions (Torcal, 2014) and the economic crisis in Portugal one decade ago that negatively influenced the political attitude (Brito Vieira et al, 2017) and the political trust (van der Meer and Hakhverdian, 2017). The e-participation tools oriented for decision making may open an interesting opportunity to allow the citizens themselves to propose and decide on local issues, which could help to recover the trust and satisfaction in representative institutions.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, welfare attitudes research has traditionally also recognized a competing hypothesis, labelled here as the ‘cost awareness hypothesis’. According to this view, heightened risk exposure can induce self-regarding reasoning and can weaken concerns for the well-being of the disadvantaged in society, thereby eroding public support for the welfare state (Brito Vieira et al 2017 ; Durr 1993 ; Sihvo and Uusitalo 1995 ). In times of hardship, citizens may become more aware of increasing costs and limited resources, thereby being more hesitant to support extensive government provision (Jensen and Naumann 2016 ).…”
Section: Theoretical Perspectives On the Impact Of The Covid-19 Crisi...mentioning
confidence: 99%
“…With regard to the general evolution of support for a BI, existing literature wavers between two contrasting theoretical expectations of how different groups react to increased risk exposure. On the one hand, when assuming that people reason more from a self-interested perspective, different experiences of the crisis could lead groups to alter their opinions on welfare provision in various ways (Brito Vieira et al 2017 ; Forma 2002 ). This so-called ‘polarization thesis’ predicts that groups that are disproportionally affected by a crisis demand more government protection, whereas the middle and upper classes may turn against generous welfare provision because they fear the costs will rise exponentially.…”
Section: Theoretical Perspectives On the Impact Of The Covid-19 Crisi...mentioning
confidence: 99%
See 2 more Smart Citations